Big Brother Brasil : um cenário observado a procura de uma estratégia de posicionamento crítico no espaço público - Cruz, Maria Amelia Maneque (Universidade do Vale do Rio do Sinos, 2007)
This paper has been developed based on the observation and analysis of Big Brother Brasil 5 program, a reality show exhibited by Rede Globo de Televisão (Globo TV Network), in channel 12, from January to March 2005. The aim was to identify the strategies that made it possible for Jean Wyllys to receive the final award. This analysis of the actions and movements was given through the techniques of Public Relations, used with the objective to construct, to keep and to manage images in the public space. The conclusion of this dissertation is that Jean Wyllys won Big Brother Brasil because he entered the program bearing in mind a well-defined strategic planning, with a set of pre-established decisions that made it possible for him to remain in the game and to win every eliminating phase. His votes always showed coherence with the situation he was facing. His tactics and strategies had been efficient and efficient they had an intention: to win the program and and receiving the award. He used the dolphin strategy,
Keywords: análise; Big Brother Brasil; programa; reality show; televisão; Big Brother Brazil; game strategies; public relations; public relations strategy; reality show; Ciências Sociais Aplicadas